1999
DOI: 10.1021/bi982952b
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Mechanism of Scytalone Dehydratase:  Site-Directed Mutagenisis, Kinetic Isotope Effects, and Alternate Substrates

Abstract: On the basis of the X-ray crystal structure of scytalone dehydratase complexed with an active center inhibitor [Lundqvist, T., Rice, J., Hodge, C. N., Basarab, G. S., Pierce, J. and Lindqvist, Y. (1994) Structure (London) 2, 937-944], eight active-site residues were mutated to examine their roles in the catalytic mechanism. All but one residue (Lys73, a potential base in an anti elimination mechanism) were found to be important to catalysis or substrate binding. Steady-state kinetic parameters for the mutants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(78 citation statements)
references
References 20 publications
2
75
0
1
Order By: Relevance
“…This is similar to the Ser and Asn proposed to bind the C6-and C8-OH groups of scytalone (20, Fig. S4) in scytalone dehydratase studies (12). This conformation also docks C1-C8 and C15-C20 of the polyketide chain in the pocket and positions the C1 thiol at the pocket entrance, where ACP would be covalently linked to C1 via a thioester bond.…”
Section: First-ring Cyclization If the Polyketide Is Cyclized At C9-c14supporting
confidence: 75%
“…This is similar to the Ser and Asn proposed to bind the C6-and C8-OH groups of scytalone (20, Fig. S4) in scytalone dehydratase studies (12). This conformation also docks C1-C8 and C15-C20 of the polyketide chain in the pocket and positions the C1 thiol at the pocket entrance, where ACP would be covalently linked to C1 via a thioester bond.…”
Section: First-ring Cyclization If the Polyketide Is Cyclized At C9-c14supporting
confidence: 75%
“…Further analysis indicates that KstA10 is homologous to NAD + -dependent nucleotide diphosphate sugar epimerases (23), which act on totally different substrates from that in KST biosynthesis. In addition, scytalone dehydratase in the fungal melanin biosynthesis is cofactor independent (18,19). However, evidence obtained from our biochemical assays suggested that the dehydration catalyzed by KstA10 is dependent on NAD(P)H (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 89%
“…Our in vitro results unequivocally demonstrated that KstA15/A16 synergistically catalyze hydroxylation of 3 to produce 5, which may serve as an intermediate during the hydroxyl regioisomerization process; thus, a dehydroxylation must be involved in the transformation from 5 to 4. To the best of our knowledge, two enzymatic dehydroxylation pathways of aromatic ring had been reported: Birch-like one electron reduction mechanism, as exemplified by 4-hydroxybenzoyl-CoA reductase, which is a Mo-flavo-Fe/S-dependent protein (16,17), and reduction-dehydration process-mediated dehydroxylation in the fungal melanin biosynthetic pathway, operated by 1,3,6,8-tetradroxynaphthalene reductase, 1,3,8-tridroxynaphthalene reductase, both belonging to the short-chain dehydrogenase/reductase (SDR) superfamily, and scytalone dehydratase (18)(19)(20). However, bioinformatic analysis revealed that neither Mo-flavo-Fe/S protein nor scytalone dehydratase homolog has been found in the KST pathway.…”
Section: Resultsmentioning
confidence: 99%
“…The ligand-binding pocket of the enzyme is a cone-shaped ␣ϩ␤ barrel, consisting of eight ␤ strands and four ␣ helixes sandwiched together. The enzyme acts independently of cofactors, prosthetic groups, or metal ions (37). In addition to its natural substrates, scytalone and vermelone, SD is also able to act on the pyrone 2,3-dihydro-2,5-dihydroxy-4H-benzopyran-4-one (DDBO), which resembles the structure of YWA1 (38).…”
Section: Discussionmentioning
confidence: 99%
“…The MIPS annotation of AurS includes the prediction of a transmembrane domain located from positions 7 to 29, and an analysis using SignalP suggests that this N-terminal sequence contains a signal peptide, which is cleaved between Ser 36 and Gln 37 . This combined with a TargetP prediction suggests that the signal peptide induces secretion of the protein to the extracellular surface of the cell (score: 0.899).…”
Section: Aurt Aurz and Aurs Are All Involved In Aurofusarinmentioning
confidence: 99%